Evaluasi Program Budidaya Jamur Tiram Dalam Meningkatkan Kemandirian Berwirausaha Warga Belajar di PKBM Abdi Pertiwi - Putri Alika; Devia Fitri Nurmahmudha; Fatihah Nurul Hayati; Arini Teduh Alam Iskandar (Peneliti.net, 2022)
The condition of the people around the city of Serang generally still have a middle to lower level of welfare. The main point of community empowerment is the creation of independence, which means being able to help oneself for their survival. PKBM Abdi Pertiwi is one of the institutions that supports community empowerment through entrepreneurship programs. PKBM Abdi Pertiwi can help the surrounding community so that the community can improve their welfare, through the mushroom cultivation entrepreneurship program. This evaluation aims to assess the success of the objectives of the entrepreneurship program organized by PKBM Abdi Pertiwi using objective-based evaluation, the evaluation method used is interviews. Sources of data derived from primary data (PKBM managers and learning residents) and secondary data (library and documentation). The evaluation instruments used were interview guides, observations, and recommendations. Data analysis techniques used are reduction, data display, drawing conclusions. The results of the evaluation that has been carried out show that the success of the program has been in accordance with the objectives carried out, reaching 80%. With that learning citizens can be said to have increased knowledge, skills, capable of entrepreneurship independently.